1994
DOI: 10.1111/j.1476-5381.1994.tb14045.x
|View full text |Cite
|
Sign up to set email alerts
|

l‐NAME, nitric oxide and jejunal motility, blood flow and oxygen uptake in dogs

Abstract: 1The effects of the inhibitor of nitric oxide (NO) synthesis, N0-nitro-L-arginine methyl ester (L-NAME), on systemic arteriil blood pressure and jejunal motility, blood flow, and oxygen uptake have been investigated in anaesthetized dogs. 2 L-NAME (cumulative doses of 0.1-20 mg kg-', i.v.) dose-dependently increased blood pressure and jejunal motility and decreased heart rate. The maximal response of these three variables occurred at doses, 3, 10 and 10mgkg-l, respectively. L-NAME (cumulative doses of 0.5-5mgk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…The vasodilatory effects of Ang- (1)(2)(3)(4)(5)(6)(7) are NOS and guanylate cyclase dependent. We then investigated the intracellular mechanisms that might be responsible for the effects of Ang-(1-7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vasodilatory effects of Ang- (1)(2)(3)(4)(5)(6)(7) are NOS and guanylate cyclase dependent. We then investigated the intracellular mechanisms that might be responsible for the effects of Ang-(1-7).…”
Section: Resultsmentioning
confidence: 99%
“…There was one additional group in which both AT1R and Mas receptor were blocked. The doses of lisinopril, candesartan, PD123319, JE049, A779, AVE0991, D-Pro 7 -Ang-(1-7), L-NAME, and ODQ were based on our laboratory's preliminary investigations and published studies (1,7,8,15,26,39,45,46). To determine whether Ang-(1-7) affected the response to another major mediator of hepatic vascular tone and to dissect out the involvement of AT1R in the Ang-(1-7) signaling pathway, we administered the ␣-adrenergic agonist MTX in two groups using the same design as for Ang II; one group of livers was perfused in the presence of the AT1R blocker candesartan and the other with candesartan plus the Mas receptor blocker A779.…”
Section: Chemicals and Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess this possibility, the influence of the NO synthase inhibitor L-NAME was investigated. A dose of L-NAME was chosen that has been previously shown to affect intestinal motility in dogs (2). The administration of L-NAME caused a decrease in gastric volume, reflecting a stomach contraction.…”
Section: Effect Of 5-ct On Conscious Dogs Before and After Vagotomymentioning
confidence: 99%
“…It has been reported that this hormone decreases or has no effect on endothelium proliferation [6,11,12,13], but it can induce nitric oxide (NO) synthesis [4]. NO is endogenously synthesized from the guanidino nitrogen atoms of L-arginine or can be produced from exogenous sources, such as nitrovasodilatators by one of several isoforms of NO synthases (NOS) [14,15]. In the circulatory system, NO is produced by a constitutively-expressed endothelial NOS isoform (eNOS) and acts as an endogenous nitrovasodilatator [16] playing a pivotal role in EC function [17,18].…”
Section: Introductionmentioning
confidence: 99%